Report From a Forum on US Heart Allocation Policy. Issue 1 (22nd December 2014) - Kobashigawa, J. A.; Johnson, M.; Rogers, J.; Vega, J. D.; Colvin‐Adams, M.; Edwards, L.; Meyer, D.; Luu, M.; Reinsmoen, N.; Dipchand, A. I.; Feldman, D.; Kormos, R.; et al.
<x xml:space="preserve">Abstract</x> Since the latest revision in US heart allocation policy (2006), the landscape and volume of transplant waitlists have changed considerably. Advances in mechanical circulatory support (MCS) prolong survival, but Status 1A mortality remains high. Several patient subgroups may be disadvantaged by current listing criteria and geographical disparity remains in waitlist time. This forum on US heart allocation policy was organized to discuss these issues and highlight concepts for consideration in the policy development process. A 25‐question survey on heart allocation policy was conducted. Among attendees/respondents were 84 participants with clinical/published experience in heart transplant representing 51 US transplant centers, and OPTN/UNOS and SRTR representatives. The survey results and forum discussions demonstrated very strong interest in change to a further‐tiered system, accounting for disadvantaged subgroups and lowering use of exceptions. However, a heart allocation score is not yet viable due to the long‐term viability of variables (used in the score) in an ever‐developing field. There is strong interest in more refined prioritization of patients with MCS complications, highly sensitized patients and those with severe arrhythmias or restrictive physiology. There is also strong interest in distribution by geographic boundaries modified according to population. Differences of opinion exist between small and large centers.